Altered profiles of serum neuroactive steroids in premenopausal women treated for alcohol addiction - Hill, Martin; Popov, Petr; Havlíková, Helena; Kancheva, Lyudmila; Vrbíková, Jana; Kancheva, Radmila; Pouzar, Vladimír; Cerný, Ivan; Stárka, Luboslav (Steroids, 2005)
Long-term alcohol consumption results in menstrual irregularities due to the inhibition of progesterone secretion. Some progesterone metabolites, including three pregnanolone isomers (PI), abate, while pregnenolone sulfate (PregS) and dehydroepiandrosterone sulfate (DHEAS) increase, alcohol tolerance. The rationale of this study was to evaluate how the neuroactive steroids reflect the impaired progesterone formation in premenopausal women treated for alcohol addiction, and whether detoxification therapy could restore female reproductive functions and psychosomatic stability by reinstatement of the steroid biosynthesis. Accordingly, serum allopregnanolone (3alpha-hydroxy-5alpha-pregnan-20-one (P3alpha5alpha)), pregnanolone (P3alpha5beta), isopregnanolone (P3beta5alpha) and epipregnanolone (P3beta5beta), progesterone, PregS, pregnenolone, 17alpha-hydroxy-pregnenolone (Preg17), 17alpha-hydroxy-progesterone (Prog17), DHEA, DHEAS, cortisol and estradiol were measured in 20 women during the therapy (start, 3 days, 14 days, 1 month, 4 months), and in 17 controls, using GC-MS or RIA and evaluated by age-adjusted ANCOVA with status and phase of the menstrual cycle (PMC) as factors, and status-PMC interaction. The patients exhibited depressed progesterone, Prog17, PI, and estradiol, a decreased progesterone/pregnenolone ratio, a decreased ratio of neuroinhibiting P3alpha5alpha to neuroactivating PregS, and an elevated PregS and PregS/pregnenolone ratio. The treatment mostly restored the indices. The reduction of neuroinhibiting pregnanolone isomers in the patients is primarily associated with the impairment in ovarian steroid biosynthesis. Nevertheless, changes in enzyme activities connected with the formation of PI and the influence of altered physiological requirements on the balance between endogenous neuroinhibiting and neuroactivating steroids are also likely. The reinstatement of serum estradiol, progesterone, and PI during the therapy demonstrates its favorable effect on both reproductive functions and the psychosomatic stability of the patients.
Keywords: Premenopause; premenopauza; Female; progesteron; Progesterone; ženské pohlaví; hydrokortison; Time Factors; časové faktory; lidé; pregnenolon; Hydrocortisone; alkoholismus; Radioimmunoassay; Stereoisomerism; stereoizomerie; dehydroepiandrosteron; Dehydroepiandrosterone Sulfate; Pregnanolone; Alcoholism; Dehydroepiandrosterone; pregnanolon; plynová chromatografie s hmotnostně spektrometrickou detekcí; steroidy; Gas Chromatography-Mass Spectrometry; Estradiol; radioimunoanalýza; dehydroepiandrosteronsulfát; Pregnenolone; Steroids; estradiol; Humans